USE OF TECHNOLOGICAL GADGETS IN INSTRUCTIONAL SUPERVISION AND ACADEMIC PERFORMANCE OF STUDENTS IN PRIVATE SECONDARY SCHOOLS IN OWERRI EDUCATION ZONE I (UNIZIK Journal of Educational Management and Policy, 2024)
This study investigated the use of technological gadgets on instructional supervision and academic performance of students in private secondary schools in Owerri education zone I. The correlational research design wasused in this study. The population of the study is 6,904. The sample size is690, drawn using simple random sampling technique.  Rating scales and academic profoma were used as the instruments for data collection in this study.  The instrument was developed by the researchers after a thorough review of literature while the academic profoma was used to collect the students’( Junior Secondary School 3 (JSS3) promotion examinations results.  The instrument covered the specific objectives of the study. The instrument was validated by five specialists. The reliability of the instrument was tested through a test re-test method using the Pearson Product Moment Corelation Coefficient (PPMCC) and a reliability co-efficient of 0.74 was realized showing that the instrument was reliable for the study.  The researchers computed the raw scores, by using SPSS, 21.0 version.  Findings showed among others that there is a very high positive relationship between principal-implemented instructional supervision and students’ academic performance in  private secondary schools, in Imo State. Based on the findings, it was concluded that principal-implemented instructional supervision and supervisor-implemented instructional supervision are effective in improving students’ academic performance in private private secondary schools
Keywords: gadgets, technological, performance, supervision.